KONSTRUKSI MEDIA, MULTIKULTURALISME, DAN EKSISTENSI UNDANG -UNDANG PENYIARAN DI INDONESIA - Agus Maladi Irianto (Faculty of Law, Universitas Diponegoro, 2011)
Media has developed not only to represent knowledge, idea and point of view which then it develops a solid structure as well as in the stable society where there is no conflict of interest. The recent media has build a social reality from an industry that is presented to a community which is dynamic, contemporer and constantly changing. The sibbholeth of